"This case is about you and your future": Towards Judgments for Children. Issue 5 (14th May 2020) - Stalford, Helen; Hollingsworth, Kathryn
Abstract: A handful of 'child‐friendly' judgments have emerged in the UK in recent years, attempting to adopt a child‐centred approach to the decision‐making stage of the legal process. Most notable is Sir Peter Jackson's judgment in Re A: Letter to a Young Person which, in taking the form of a letter to the child, has been applauded as a model of how to achieve 'child friendly justice'. This article examines how and why the form and presentation of judicial decisions is an important aspect of children's access to justice, considering not just the potential but the  duty  of judges to enhance children's status and capacities as legal citizens through judgment writing. We identify four potential functions of judgments written for children (communicative, developmental, instructive and legally transformative), and call for a radical reappraisal of the way in which judgments are constructed and conveyed with a view to promoting children's access to justice.